Free Hand-Drawn Sketch Segmentation - Sun, Zhenbang; Wang, Changhu; Zhang, Liqing; Zhang, Lei (European Conference on Computer Vision (ECCV), 2012)
In this paper, we study the problem of how to segment a freehand sketch at the object level. By carefully considering the basic principles of human perceptual organization, a real-time solution is presented to automatically segment a user’s sketch during his/her drawing. First, a graph-based sketch segmentation algorithm is proposed to segment a cluttered sketch into multiple parts based on the factor of prox- imity. Then, to improve the ability of detecting semantically meaningful objects, a semantic-based approach is introduced to simulate the past experience in the perceptual system by leveraging a web-scale clipart database. Finally, other important factors learnt from past experience, such as similarity, symmetry, direction, and closure, are also taken into account to make the approach more robust and practical. The proposed sketch segmentation framework has ability to handle complex sketches with overlapped objects. Extensive experimental results show the effectiveness of the proposed framework and algorithms.